2016
DOI: 10.1371/journal.pone.0167426
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Selected Chemical Cell Wall Components in the Embryogenic Callus of Brachypodium distachyon

Abstract: Brachypodium distachyon L. Beauv. (Brachypodium) is a species that has become an excellent model system for gaining a better understanding of various areas of grass biology and improving plant breeding. Although there are some studies of an in vitro Brachypodium culture including somatic embryogenesis, detailed knowledge of the composition of the main cell wall components in the embryogenic callus in this species is missing. Therefore, using the immunocytochemical approach, we targeted 17 different antigens of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 73 publications
7
51
0
Order By: Relevance
“…In addition, during the somatic embryogenesis of Trifolium nigrescens Viv., it was demonstrated that the low methylesterified homogalacturonan (HG), which is recognised by the JIM5 antibody, and the arabinan from side chains of rhamnogalacturonan I (RG I), which is recognised by the LM6 antibody, were detected in the embryogenic sectors of the explant (Pilarska et al 2013). Moreover, the chemical composition of the cell walls and ECM of a Brachypodium callus displayed spatial differences that correlated with the embryogenic character of the cells (dense cytoplasm, high nucleus/cytoplasm ratio, large nucleoli), thus indicating that the distribution of pectins, AGPs and hemicelluloses can be used as molecular markers of the embryogenic cells (Betekhtin et al 2016).…”
Section: Jim20mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, during the somatic embryogenesis of Trifolium nigrescens Viv., it was demonstrated that the low methylesterified homogalacturonan (HG), which is recognised by the JIM5 antibody, and the arabinan from side chains of rhamnogalacturonan I (RG I), which is recognised by the LM6 antibody, were detected in the embryogenic sectors of the explant (Pilarska et al 2013). Moreover, the chemical composition of the cell walls and ECM of a Brachypodium callus displayed spatial differences that correlated with the embryogenic character of the cells (dense cytoplasm, high nucleus/cytoplasm ratio, large nucleoli), thus indicating that the distribution of pectins, AGPs and hemicelluloses can be used as molecular markers of the embryogenic cells (Betekhtin et al 2016).…”
Section: Jim20mentioning
confidence: 99%
“…It has been postulated that the residues of galacturonic acid that are present in the chains of low or unmethyl-esterified HG are cross-linked with calcium cations, thus forming a "pectin gel", which, in turn, may contribute to wall stiffening (Willats et al 2001a;Jiang et al 2005;Caffall and Mohnen 2009;Hongo et al 2012). The presence of the above-mentioned pectic epitopes in the ECM has been observed not only on the surface of the somatic embryos and embryogenic callus but also on the OC in different plant species (Konieczny et al 2007;Popielarska-Konieczna et al 2008;Betekhtin et al 2016). Chapman et al (2000) stated that the non-esterified pectins that are present in the extracellular matrices may be responsible for maintaining embryonic cell adhesion and that the occurrence of the layer that covers the cell itself could spatially limit cell division.…”
Section: Chemical Composition Of Ecm and Cell Wall As A Marker For DImentioning
confidence: 99%
See 1 more Smart Citation
“…Embryogenic cells have the typical features of undifferentiated cells such as a small or poorly developed vacuole, dense cytoplasm and a nucleus that usually has one and occasionally two nucleoli [98]. Mitoses are also occasionally present [99]. In contrast, non-embryogenic calli have parenchymatous or differentiated cells that are larger and highly vacuolated.…”
Section: Factors That Affect the In Vitro Propagation Of Grassesmentioning
confidence: 99%
“…An embryogenic callus that was formed by cells that had been derived from the protodermal-dividing cells of the scutellum [98] initially had typical meristematic features and a high level of protein accumulation, which is connected with the acquisition of a competent state [100]. Embryogenic calli have an extracellular matrix on the surface of the calli cells (ECMSN), which is composed of the arabinogalactan proteins (AGPs) and pectins [99]. The pectins, AGPs and hemicelluloses can be used as molecular markers of the embryogenic cells.…”
Section: Factors That Affect the In Vitro Propagation Of Grassesmentioning
confidence: 99%